Mobilizing Cash Waqf through Sharia Crowdfunding Platforms: A Multi-Country Comparative Study - Syalwa Azahra; Muhammad Rasyid; Saniah Lubis; Muhammad Radhefa Mumtaza; Nur Indah Permata Sari (Jurnal Elsyakhshi, 2025)
The digital transformation of the Islamic finance sector has introduced new mechanisms for mobilizing Islamic social funds, particularly cash waqf, which has traditionally faced challenges related to accessibility and distribution efficiency. Sharia crowdfunding platforms, as part of Sharia-compliant financial technology (fintech), enable broader participation and democratization of modern Islamic philanthropic practices. This study aims to examine the effectiveness of Sharia crowdfunding platforms in mobilizing cash waqf through a multi-country comparative qualitative study. Using content analysis of regulatory frameworks, platform governance documents, and publicly available institutional reports, the study identifies key factors influencing platform performance across different socio-economic and regulatory contexts. The findings reveal significant cross-country variations, with Malaysia and the United Arab Emirates demonstrating higher levels of effectiveness, while Indonesia shows strong performance in terms of mass donor participation. Regulatory frameworks, technological infrastructure, and socio-religious characteristics emerge as interrelated pillars shaping the success of cash waqf mobilization through crowdfunding platforms. The study contributes theoretically to the development of Islamic social finance literature and provides practical implications for policymakers, platform developers, and Islamic philanthropic institutions in strengthening an inclusive and sustainable Sharia fintech ecosystem.